Between Two Plenums China's Intraleadership Conflict, 1959-1962 - Joffe, Ellis (Michigan Monographs In Chinese Studies, 2020)
The origins of the Cultural Revolution are still shrouded in uncertainty. Crucial questions either remain unanswered or have been given answers which derive from conflicting interpretations. To what period can the direct origins of the Cultural Revolution be traced? What issues, if any, divided the leadership, and how deep were these divisions? What was the state of power relations and what was Mao's position? Why did developments in the period preceding the Cultural Revolution reach a climax in such a convulsion? Between Two Plenums examines these questions as they apply to the years 1959-1962. At base, the perspective of pre-Cultural Revolution politics adopted therein is that of "conflict" rather than "consensus." From this vantage point, the Eighth and Tenth Plenums loom in retrospect as important watersheds in the development of the intraleadership conflict which culminated in the great upheaval.